Digital Marketing Strategy and Brand Loyalty among Customers of Airtel Network, Kenya - Aliata, Victor Lusala (European Journal of Business and Strategic Management, 2025)
Purpose: Digital marketing encompasses all marketing efforts that use an electronic device or internet. As digital platforms are increasingly incorporated onto marketing plans and everyday life and as people use digital devices instead of visiting physical shops, digital marketing is becoming more prevalent and efficient. According to Communications Authority of Kenya (CAK), Airtel networks Kenya ltd has had its market share increase marginally from 21.4% in 2018 to 27.2 in 2020.It is uncertain if the increase can be attributed to its digital marketing strategy thus the paper explores the effect of digital marketing strategy on brand loyalty among customers of Airtel network Kenya. Methodology: Primary data was collected from a target population of 100 third year Bachelor of Business Administration (BBA) students from Tom Mboya University, Kenya. Study sample of 80 was extracted for the study using Yamane (1967). Purposive sampling technique was used to collect data. Those targeted are the ones assumed to be subscribers of airtel network ltd, Kenya. Secondary data was accessed through Airtel’s network limited annual reports. The study utilized correlation research design. Findings: Study findings revealed that digital marketing accounts for 41.0% significant variance in customer loyalty, (R2=.410, F (1, 78) =55.934, p<.05). It is also clear that digital marketing has a positive significant effect on customer loyalty (β=.646, p<.05). This implies that for every improvement in digital marketing, customers become more loyal. Therefore, digital marketing has a positive and significant influence on Airtel subscribers’ customer loyalty. Unique Contribution to Theory, Practice and Policy: The study recommends an enhancement of the digital marketing strategies in Airtel Kenya. Emphasis should be to push most of the services into the digital platform. This will improve service delivery and further positive implication on brand loyalty of Airtel. This will also lead to positive word of mouth advertisement which will aid in introducing new customers on board.in order to encourage the subscribers carry out snow balling reference to others and so increase customer subscription.